2020
DOI: 10.1200/jco.2020.38.15_suppl.e15528
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs involved in immune response as prognostic markers in early and metastatic breast cancer.

Abstract: e15528 Background: MicroRNAs (miRNAs) are involved in the regulation of immune response and have an important role in immune escape. We analyzed the expression levels of plasma miR-10b, miR-126, miR-19α, miR-20α and miR-155, which regulate tumor-immune interactions and investigated their prognostic implications in patients with early (eBC) and metastatic (mBC) breast cancer. Methods: Blood samples were obtained before treatment from 140 and 64 patients with eBC and mBC, respectively. Plasma miRNA expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We herein show that low plasma miR-10b expression was a predictor for shorter DFS in eBC and for shorter PFS in mBC patients. Furthermore results from our lab showed that the expression levels of miR-10b in the plasma were lower in relapsed compared to non-relapsed eBC patients ( Papadaki et al, 2020b ). Our findings suggest that high miR-10b expression levels in the plasma could reflect effective tumor-immune cell interactions in the TME associated with favourable patients’ outcomes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We herein show that low plasma miR-10b expression was a predictor for shorter DFS in eBC and for shorter PFS in mBC patients. Furthermore results from our lab showed that the expression levels of miR-10b in the plasma were lower in relapsed compared to non-relapsed eBC patients ( Papadaki et al, 2020b ). Our findings suggest that high miR-10b expression levels in the plasma could reflect effective tumor-immune cell interactions in the TME associated with favourable patients’ outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…We have previously shown that the above miRNAs are differentially expressed among healthy women and eBC patients ( Papadaki et al, 2020b ). In addition, a differential expression pattern was encountered among relapsed and non-relapsed patients with early disease ( Papadaki et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven miRNAs were differentially expressed between BC patients with and without recurrences, including four miRNAs upregulated (miR-21-5p, miR-375, miR-205-5p, and miR-194-5p) and three miRNAs downregulated (miR-382-5p, miR-376c-3p, and miR-411-5p) [ 456 ]. The association of miR-19a, miR-20a, miR-126, and miR-155 can discriminate against the metastatic outcome of BC patients [ 457 , 458 ].…”
Section: Exosomes As Relevant Breast Cancer Biological Markersmentioning
confidence: 99%